2019
DOI: 10.1039/c9gc01857c
|View full text |Cite
|
Sign up to set email alerts
|

Tuning zirconia-supported metal catalysts for selective one-step hydrogenation of levoglucosenone

Abstract: One-pot selective hydrogenation of levoglucosenone to Cyrene and levoglucosanol was successfully carried out by using Pd/ZrO2 and Pt/ZrO2 catalysts, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The formation of the PtIr alloy on the mesoporous carbon also prevents the successive In our previous work [13], we demonstrated that the PtIr alloy combined the hydrogenating capacity of Pt and the hydrogenolysis capacity of Ir. The high activity and selectivity of Pt for C = O hydrogenation, is controlled by the presence of Ir to improve the selectivity to DMF, thus preventing the subsequent hydrogenation [63,64]. This fact was understood in terms of the rapid conversion of BHMF via MFA to give DMF through a hydrogenolysis site provided by Ir in the bimetallic alloy.…”
Section: Catalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the PtIr alloy on the mesoporous carbon also prevents the successive In our previous work [13], we demonstrated that the PtIr alloy combined the hydrogenating capacity of Pt and the hydrogenolysis capacity of Ir. The high activity and selectivity of Pt for C = O hydrogenation, is controlled by the presence of Ir to improve the selectivity to DMF, thus preventing the subsequent hydrogenation [63,64]. This fact was understood in terms of the rapid conversion of BHMF via MFA to give DMF through a hydrogenolysis site provided by Ir in the bimetallic alloy.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…In this way, the charge density on the bimetallic sites decreases. The high rate of hydrogenation of the C = O bond by Pt [63][64][65][66], makes this reaction difficult to control and that the reaction continues to form undesired products. The presence of a second metal forming an alloy, as is the case with Ir, favors the control of the reaction towards the formation of DMF.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Cyrene is also used as a synthetic raw material and for extracting valuable bioactive compounds, such as hesperidin and rutin . Deeper hydrogenation converts LGO into levoglucosanol and then tetrahydrofurandimethanol (THFDM). , The hydrogenolysis products of THFDM, 1,2,6-hexanetriol and 1,6-hexanediol, are widely used in industry for polyester and polyurethane production. Huber’s research group also commenced studies on the conversion of LGO into 5-hydroxymethylfurfural (HMF). , HMF is one of the most promising platform chemicals in sugar chemistry with great industrial potential and a broad range of applications .…”
Section: Introductionmentioning
confidence: 99%
“…7,9,18,19 Also, when adding Cyrene to water, a powerful hydrotrope is created, the central aspect to this phenomenon being Cyrene's geminal diol. 20 Other potentially useful LGOderived molecules are Lgol, 17,21,22 tetrahydrofuran-dimethanol 22,23 (THFDM), hexane-1,2,6-triol (HTri), 24,25 hexane-1,6diol 22,25−29 (1,6-HD), and tetrol. 28,30 The main reactants and products of interest for this work are shown in Figure 1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…LGO is a highly functionalized molecule that can be used in asymmetric synthesis, , to create chiral pure pharmaceutical intermediates, , and for the synthesis of chemicals useful to the creation of polymers, such as hydroxymethylfurfural , (HMF). It has equally been established that dihydrolevoglucosenone (Cyrene) obtained from LGO hydrogenation is a benign low-toxicity polar aprotic solvent with similar properties as dimethylformamide (DMF) or N -methylpyrrolidone (NMP). ,,, Also, when adding Cyrene to water, a powerful hydrotrope is created, the central aspect to this phenomenon being Cyrene’s geminal diol . Other potentially useful LGO-derived molecules are Lgol, ,, tetrahydrofuran-dimethanol , (THFDM), hexane-1,2,6-triol (HTri), , hexane-1,6-diol , (1,6-HD), and tetrol. , The main reactants and products of interest for this work are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%